The Myth as a Means of Construction of SocialCultural Reality of the Man of the Crowd - Babajanyan, Levon (Bulletin of Yerevan University E: Philosophy, Psychology, 2015)
In the article, the ideas and ideals of the project of modernity considered as the basics of construction of the modern socialcultural reality, which are based on the principle of rationality. But because of the modernization the demythologized, demystified modern social-cultural space is incurred of the invasive activity of the man of the crowd, which is the offspring of the modernised civilization. The man of the crowd obliges the modern civilization to accept its own social-cultural reality, because of what the myths and archetypes, which were hidden in the archaic layers of collective unconsciousness of the mankind, emerge in the modernized, rationalized current civilization. So, in the modern world myths and mythical consciousness construct the social-cultural reality of the man of the crowd.
Keywords: The Man of the Crowd, Project of Modernity, Desacralization, Myth, Mythical Consciousness, Construction of the Social-Cultural Reality